Evaluation of Indexation Consistency in Publisher Subject Metadata - Tolare, Jessica Beatriz; Cruz, Maria Carolina Andrade; Fujita, Mariângela Spotti Lopes (Central European Journal of Educational Research, 2022)
This work aims at evaluating the indexing of subject metadata published on the MercadoEditorial.org platform. The goal: to verify if the indexing is consistent. First, analysis was done of the tools available on the platform for assigning keywords, and, afterwards, publishers on the platform were documented and verified by running intrinsic evaluation for interconsistency. This was all done to compare the indexing of one work by four authors. The authors were Ciranda Cultural, IBEP, Excelsior Editora, and Via Leitura. The chosen book was “The Alienist” by Machado de Assis, a classic in Brazilian literature. The result of the indexing analysis was that publishers gave keywords such as title, author’s name, characters’ names, names of other books, and excessively used and repeated words. The last category was further broken down being with or without accentuation, being in the singular or plural form. Other terms were assigned that were related to university entrance exams. Thus, it can be concluded that an absence of vocabulary control can make retrieval of a work difficult, simply by assigning terms that inadequately define the subject of the book, and by lacking semantic, syntactic, and morphological standardization among the terms.